2019
DOI: 10.2478/pjg-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

3D Interpretation of Resistivity Data for Groundwater Potential Assessment of Pakhli Plain, Mansehra District, Pakistan

Abstract: The present research describes a method of combining geostatistical analysis with geophysical inversion of electrical resistivity data conducted in Pakhli Plain, northwestern Himalayas, Pakistan. The raw data has been collected from the Technical Report VII-I on Ground Water Resources in Pakhli Plain, Mansehra District. Subsequently, the data has been deciphered and broadened from one dimensional resistivity data into a 2D model that can be entirely visualized and deduced in a spatial sense. Interpretation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, the results revealed that low general transmissivity of the sediments, which means that there are deprived conditions for commercial groundwater production in the area. In specific, the main objectives of this study were groundwater potential exploration and 3D modeling of underground resistivity by means of low resistivity zones distribution ( Javed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results revealed that low general transmissivity of the sediments, which means that there are deprived conditions for commercial groundwater production in the area. In specific, the main objectives of this study were groundwater potential exploration and 3D modeling of underground resistivity by means of low resistivity zones distribution ( Javed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%